The use of recovery methods post-exercise - Reilly, T.; Ekblom, B. (Journal of Sports Sciences, 2005)
Competitive soccer engages many of the body`s systems to a major extent. The musculoskeletal, nervous, immune and metabolic systems are stressed to a point where recovery strategies post-exercise become influential in preparing for the next match. Intense activity at a 7-day training camp causes participants to experience lowered concentrations of non-killer cells and T-helper cells. Two consecutive games in 24 h produce disturbances in the testosterone - cortisol ratio. When competitive schedules are congested, the recovery process should be optimized for performance capabilities to be restored to normal as soon as possible. There is evidence that glycogen stores are reduced near to depletion at the end of a soccer game and that a diet high in carbohydrates can aid recovery. Water alone is not the best means of restoring body fluids, since carbohydrate-electrolyte drinks display better intestinal absorption and reduce urine output. Some relief from muscle soreness may be achieved by means of a warm-down. Deep-water running regimens can replace conventional physical training in the days after competition. Massage, cryotherapy and alternative therapies have not been shown to be consistently effective. It is concluded that optimizing recovery post-exercise depends on a combination of factors that incorporate a consideration of individual differences and lifestyle factors. The procedures to facilitate recovery processes should start immediately the game or training finishes. Match administrators and tournament planners should consider the stressful consequences for players in periods of congested fixtures and alleviate the physiological strain as far as possible by allowing 72 h between competitive games. This frequency of competition is unlikely to be sustainable in the long term.